Optimization of key gear parameters to reduce weight - Voropay, Alexey; Koriak, Olexandr; Bogdan, Dmytro; Neskreba, Eduard; Воропай, Олексій Валерійович; Коряк, Олександр Олексійович; Богдан, Дмитро Іванович; Нескреба, Едуард Євгенійович (Харківський національний автомобільно-дорожній університет, 2023)
Problem. The problems of designing, and especially improving, mechanical gears are of key importance in modern mechanical engineering and automotive transport. Gear transmissions are quite widespread relative to other mechanical transmissions because they have a number of crucial advantages. Gear transmissions are widely used in a variety of drives for vehicle components and assemblies, with modern development trends aimed at reducing their weight and size. As the size of the transmission decreases, the dimensions of other parts and assemblies also decrease, and, accordingly, their cost. Therefore, research related to the study of the interdependence of the main parameters of gears for the purpose of their further optimization does not lose its relevance. Goal. The main purpose of this work is to study the dependence of the mass and dimensions of the gears under study on their main parameters. Knowing the influence of various characteristics on the mass, it is possible to provide recommendations for the design of gears to achieve their optimal (smallest) dimensions, which leads to a number of significant advantages. Methodology. First of all, a rather detailed analysis of the scientific literature is performed in order to identify the main statements regarding the influence of certain parameters on the mass and dimensions of the designed gear. The very dependencies of the gear mass on its various characteristics are found by applying a numerical method that is entirely based on the known design dependencies for the design calculation of gears. Also, to compare the results obtained analytically, the method of calculating the mass and dimensions by creating 3D models of gears in the "Autodesk Inventor" environment is used in the work. Results. Based on the results obtained, it can be noted that, ceteris paribus, including gear load, the weight is almost independent of the module and the relative width ratio. At the same time, in some cases, a particular standard value can significantly affect the weight of the gear, i.e., by selecting specific values, it is possible to reduce the weight of the gear by about 15-25%. Originality. Useful results were obtained using a relatively affordable method. The research was conducted both analytically and with the use of modern computer-aided design systems. Practical value. The proposed recommendations for the rational choice of some characteristics of gears will reduce the weight and dimensions of the mechanical drive.
Оптимізація основних параметрів зубчастих передач з метою зменшення маси
Keywords: gear; optimization; face-width factor; gear weight; gear dimensions; gear ratio; зубчаста передача; оптимізація; коефіцієнт ширини зубчастого вінця; маса передачі; передатне відношення; 629; 10.30977/AT.2219-8342.2023.52.0.04